How Spiritualization of Maritime Science Learning in Vocational Higher Education is Carried Out? - Aufi, Ahmad Umam; Kumara, Rahindra Bayu; Kurniawan, Fajarsari; Alimatussa'diyah, Alimatussa'diyah; Harsono, Prijo (Jurnal Pendidikan Karakter, 2025)
The revitalization of vocational education is suspected of only highlighting the cognitive and psychomotor aspects in preparing human resources in the world of work. In fact, the affective aspect is a crucial aspect in the goals of national education that needs attention. This study aims to examine the implementation of vocational learning within the framework of revitalizing vocational education with a spiritualization perspective. This study describes the process of learning maritime science in Vocational Higher Education (PTV) and analyzes the spiritualization process in it as a reference for a spiritual-based vocational learning revitalization model. As a field research, a qualitative approach and spiritualization of vocational science were used in this study. The data collection techniques used participant observation, interviews, and documentation, while the analysis technique used qualitative analysis. The results of this study indicate that the ship maneuvering and control course at Polimarin has undergone a spiritualization process at the planning, implementation, and evaluation levels of learning. Spiritual aspects, especially the values of monotheism and welfare, are integrated in depth so that students understand spiritual responsibility in making professional decisions, as well as the importance of maintaining safety and the environment. The implementation of vocational learning at Polimarin can be used as an initial reference for the spiritualization model of vocational learning.